Effects Of Catharanthus Roseus Aqueous Extract On Jurkat Cells And Normal Peripheral Blood Mononuclear Cells - Ahmad, Nor Hazwani (2013)
The objective of the present study was to evaluate the effects of crude aqueous extract of C.roseus leaves on Jurkat cell line (leukemic T-cells) and normal peripheral blood mononuclear cells (PBMCs). Analytical high performance liquid chromatography (HPLC) was used to obtain the concentration of vinblastine in the C.roseus extract while the identification of selective compounds was determined by comparing the UV spectra of each compound with standards of compounds previously identified in C.roseus. The analytical data indicated the concentration of vinblastine was 1636 ± 0.2 μg g-1 of aqueous extract, equivalent to 445.6 ± 0.06 μg g-1 of dried leaves. Additionally, four of the alkaloids were identified as serpentine, vindoline, catharanthine and vindoline. The cytotoxicity effects of the extract on Jurkat cells and normal PBMCs were first examined by MTS [3-(4,5-dimethylthiazol-2-yl)-5(3- carboxymethoxyphenyl)-2-(4- sulfophenyl)-2H-tetrazolium] assay. The C.roseus extract was found significantly inhibited the proliferation of the Jurkat cells and also induced the proliferation of normal PBMCs. The cytotoxicity effect on Jurkat cells was demonstrated with IC50 values of 2.55 μg/ml and 2.38 μg/ml at 48 h and 72 h, respectively. Maximal cell proliferation was observed in PBMCs incubated with 1000 μg/ml of the C.roseus extract at various incubation times for different blood donor.